Mastering the art of manga : learn to draw manga step by step with over 1000 illustrations - Tim Seelig; Yishan Li; Rik Nicol; Andrew James (: Hermes House, 2010)
A comprehensive and detailed guide to drawing manga, suitable for both beginners and experienced artists. An introduction to materials and equipment as well as step-by-step instructions on how and when to use them. Also includes an historical overview of both manga and anime.